Digital Curation in Early Childhood: Parental Mediation and Content Quality Over Screen Duration - Deasy Anggriani Sumantri; Rahayu Khairiah (Jurnal Ners, 2026)
Screen time exposure has integrated into the lifestyle of preschool children. While excessive screen duration is frequently blamed for developmental delays, evidence suggests that the quality of parental mediation and program content play a more crucial role in shaping a child's language and social skills. Objective: To analyze the correlation between screen time duration, parental mediation quality, and program content quality with language and social interaction skills among preschool children. Methods: A quantitative study using a cross-sectional design was conducted. The sample consisted of 60 pairs of parents and preschool children selected through total population sampling at a Kindergarten. Data were collected using questionnaires alongside standardized developmental screening tools, then analyzed using Chi-Square and Fisher's Exact tests (α < 0.05) and Odds Ratio (OR). Results: Univariate analysis revealed that 70% of children exceeded the recommended screen time, 25% were suspected of language impairment, and 31.7% of social interaction difficulties. Bivariate analysis demonstrated no significant relationship between screen time duration and language skills (p=0.347) or social skills (p=0.904). Conversely, a significant relationship was found between low parental mediation and suspected language delay (p=0.004) (OR=8.0) as well as social difficulties (p=0.028) (OR=4.1). Poor program content was also significantly associated with suspected language delay (p=0.003) (OR=8.0) and social difficulties (p=0.007) (OR=5.6). Conclusion: Screen duration is not the primary risk factor for developmental issues in this preschool sample. The most substantial determinants are active parental mediation and high-quality educational content. Pediatric nurses should shift their educational focus from merely restricting screen hours to optimizing verbal co-viewing methods and digital content curation within families.